41 A Modified Delphi Consensus Approach to Clinical Guidelines for Tardive Dyskinesia. (12th March 2019) - Caroff, Stanley N.; Citrome, Leslie; Meyer, Jonathan; Riggs, Kimberly; Sajatovic, Martha; Lundt, Leslie; Ketter, Terence A.
Abstract: Objective: Vesicular monoamine transporter 2 (VMAT2) inhibitors are the first class of drugs approved to treat tardive dyskinesia (TD). With the recent approval of these medications, a modified Delphi process was implemented to address the need for updated clinical guidelines for TD screening, diagnosis, and treatment. Methods: A Steering Committee of 11 TD experts met in a Nominal Group meeting format to discuss/prioritize questions to be addressed about TD and identify individuals to be invited to serve as Delphi survey panelists. Two survey rounds were conducted anonymously; responses were collected, collated, and analyzed. Respondent agreement was defined a priori by the Steering Committee as unanimous (100%), consensus (75–99%), or majority (50–74%). For questions using a 5-point Likert scale, agreement was based on percentage of respondents choosing ≥4 ("agree completely" or "agree"). Round 1 survey included questions on TD screening, diagnosis, and treatment. Round 2 questions were refined per panelist feedback and excluded Round 1 questions with <25% agreement (deemed unlikely to achieve consensus) and some questions that already achieved consensus (>75% agreement). Results: Online surveys were sent to 60 individuals; 29 agreed to participate as panelists (23 psychiatrists; 6 neurologists). Respondents unanimously agreed (100%) that all patients currently taking dopamine receptor blocking agents (DRBAs) should be screened for TD, and that the Abnormal Involuntary Movement Scale (AIMS) is the standard structured assessment for monitoring severity of TD. There was consensus (76%) that a semi-structured assessment could be used for more frequent routine TD screening. Respondents unanimously agreed that treatment with first generation antipsychotics, older age, and longer cumulative exposure to antipsychotics were risk factors for TD. For TD diagnosis, consensus (89%) was reached that a patient with an AIMS score >2 (mild) affecting 1 body area should be considered as having possible TD; consensus (93%) was also reached that TD was most often evident in orofacial musculature, although other body areas may be affected and should not be neglected. Consensus was not reached on minimum cumulative duration of DRBA exposure for TD diagnosis, but a majority (70%) agreed that minimum cumulative exposure of 1month may be sufficient. For TD treatment, unanimity or consensus was reached on 4 strategies to consider: discussion of treatment options with patients/caregivers (100%), modification of antipsychotic regimen (100%), treatment with VMAT2 inhibitor (100%), and modification of anticholinergic regimen (86%). Conclusions: Using a Nominal Group and modified Delphi process, consensus was reached within 1−2 rounds on several key aspects of TD screening, diagnosis, and treatment. This process may offer an expedient method to identify gaps in agreement and facilitate updated management guidelines. Funding Acknowledgements: Sponsored by Neurocrine Biosciences, Inc.